Intuitionistic Fuzzy Ideals of KU-Semigroups - Kareem, Fatema F.; Talib, Sally A. (Iraqi Journal of Science, 2020)
In this work, we introduce an intuitionistic fuzzy ideal on a KU-semigroup as a generalization of the fuzzy ideal of a KU-semigroup. An intuitionistic fuzzy k-ideal and some related properties are studied. Also, a number of characteristics of the intuitionistic fuzzy k-ideals are discussed. Next, we introduce the concept of intuitionistic fuzzy k-ideals under homomorphism along with the Cartesian products.